El universalismo cristiano en Hans Urs von Balthasar a propósito de su encuentro con Karl Barth - Rolle, Carlos Ignacio Casale (Teocomunicação)
The idea of the Christian universalism is a key-subject of Balthasar’s theology. The proprium of this autor appears more clearly analysing the distance in the subject of analogia entis and the natural theology which Barth maintains. A basic element of Bathasar’s reflection about the Christian universalism has its roots in the origin of the assertion that the creation in Christ is united with the contemplation of the cosmic Christ and with the will to emphasize the universal character of the salvation happened in Christ (the concretum universale). Thus the approach is a profound comprehension of the salvation “in Christ”. The Chalcedonic formula enlarged since the fourth Lateran Council becomes a “law” for the interpretation of the (metaphysical) reality. Balthasar propounds in this way an ontology in those center the personal reality is situated. At the end the reader finds a prospective critique to Balthasar’s position